Pengaruh Profitabilitas, Likuiditas, Struktur Modal dan Kualitas Auditor Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan - Pristiwantiyasih Pristiwantiyasih (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
This study was conducted to analyze the effect of profitability, liquidity, capital structure and company size on the timeliness of submitting financial reports to manufacturing companies in the consumption sector listed on the Indonesia Stock Exchange for the period 2015 – 2018. The method used in sampling using purposive sampling method with a sample of obtained as many as 17 companies. This study uses multiple regression analysis using SPSS v.25 which consists of descriptive statistics, classical assumption test (normality test, multicollinearity test, heteroscedasticity test and autocorrelation test) and hypothesis testing (t test, F test and coefficient of determination). The results of this study indicate that partially the profitability and liquidity variables affect the timeliness of financial report submission, while the capital structure and auditor quality variables have no effect on the timeliness of financial report submission. Meanwhile, simultaneously, the variables of profitability, liquidity, capital structure, and quality of auditors affect the timeliness of submitting financial statements